Subterranean millipedes (Diplopoda) of the Iberian Peninsula - Reboleira, Ana Sofia P.s.; Enghoff, Henrik (Zootaxa, 2017)
We present a checklist of subterranean millipedes from the Iberian Peninsula. Among the 16 orders of millipedes present worldwide, nine are represented in the Iberian Peninsula, of which five have troglobiont species: Polyxenida, Glomerida, Polydesmida, Chordeumatida and Julida. Currently, 75 species of troglobiont millipedes are known from the Iberian Peninsula, although only 68 have been described so far. Most of this diversity occurs in Spain, while only seven species are known from Portugal, two endemic to Gibraltar, and  three in the Balearic archipelago. We compiled all of the literature and added our own records of the troglobiont millipedes known in the Iberian Peninsula.